Determination of hydroxyproline in Kalanchoe pinnata by HPLC / Nurul Nadia binti Zainal Abidin - Zainal Abidin, Nurul Nadia (2013)
Kalanchoe pinnata is an important plant which has many traditional medicinal uses. In this work, hydroxyproline was extracted from Kalanchoe pinnata. Determination of hydroxyproline in this plant was done using HPLC. Hydroxyproline is one of the element for the formation of collagen. There are three solvent composition used for extraction; 100% of water, 100% of ethanol and 50% of ethanol. It was found that combination of two solvent, ethanol and water can optimize the extraction as when comparing the concentration of hydroxyproline detected in the same extraction time, this system showed the highest concentration of hydroxyproline detected. Another parameter is the duration of maceration time, one to five hours which the time interval between analysis in one hour. The longer the time taken for extraction, the more hydroxyproline extacted from the sample.